KESENJANGAN EKSPEKTASI AUDITOR INTERNAL DENGAN AUDITEE - Ika Rossi Agustin; Rachma Agustina (BAJ: Behavioral Accounting Journal, 2021)
The research carried out aims to determine whether there is a gap in expectations of audit quality and independence between auditees, namely the village government of Jombang district and internal auditors who are under the inspectorate in Jombang district. By using quantitative research methods and collecting data in the form of a questionnaire, then processing the data with SPSS and analyzing the data using descriptive analysis and independent t-test. The research results show that there is a gap in expectations between the Government Internal Supervisory Apparatus and the audited party related to the independence of the internal auditor, as well as a gap in expectations between the Government Internal Supervisory Apparatus and the audited party related to audit quality.